Water-sustainable feeding strategies in post-weaning piglets: effects of sorghum-based diets on growth performance and gut health - Palumbo, Francesco; Correa, Federico; Laghi, Luca; Zurru, Antonio; Trevisi, Paolo; Luise, Diana (Frontiers in Animal Science, 2025)
The environmental sustainability of feed ingredients, including water use, plays a central role in reducing the footprint of pig production. Sorghum, due to its nutritional value and tolerance to hydric stress, can represent a valid alternative to corn. This study aims to provide a comprehensive evaluation of sorghum, as a complete replacement for corn in post-weaning piglet diets, uniquely applying an integrated multi-omics approach (microbiota 16S rRNA sequencing and 1H-NMR metabolomics) to investigate effects on growth performance and gut health. At weaning (d0), 522 pigs were assigned to one of 3 diets: Control (CTR), sorghum (SO), and extruded sorghum (EX_SO). At d0, d7 and d28 pigs were weighed, ear and tail lesions were scored and fecal samples collected for microbiota, metabolomics, and dry matter (DM) analysis. Feed intake (FI), behavior measurements (BMs) and environmental gases were recorded on d7, d14 and d28. The diet did not affect the BW (p>0.10), average daily gain (ADG; p>0.10) and FI. At d28, the feed to gain ratio (p=0.09) and the fecal DM (p=0.08) tended to be 4.1% lower and 22% higher respectively in the SO group compared with the CTR. Lesions and BMs did not differ. At d7, Oscillospira (p<0.01), was more abundant in the CTR than EX_SO; 2-Oxogutarate, Acetoin, 2-Methyl 3-Ketovalerate, 3-Methyl 2-Oxovalerate were more abundant in the EX_SO than CTR. At d28, the diet affected the beta-diversity (p=0.05); Olsenella was more abundant in the CTR than in the SO (p<0.01), Olsenella (p=0.01) and Ligilactobacillus (p=0.01) were more abundant, while Anaerovoracaceae_Family XIII UCG-001 (p=0.01) was less abundant in the CTR group than EX_SO; Shuttleworthia (p=0.02) and Syntrophococcus (p<0.01) were more abundant in the SO than in the EX_SO; butyrate, propionate and valerate were more abundant in the EX_SO than CTR (p<0.05). In conclusion, this study demonstrates that the complete replacement of corn with sorghum (12% total inclusion) does not impair post-weaning piglet performance, health and welfare under commercial conditions. The extrusion process promoted the modulation of microbial activity and metabolites in large intestine. Results support sorghum as a sustainable alternative; further studies should assess resistant starch and integrate multi-omics.